POLA PENYELENGGARAAN PENDIDIKAN NEGARA BERKEMBANG DAN MAJU DI ASIA TENGGARA - Farah Hasanah Noor; Siti Rahmatullisa; Saipul Annur; Ade Rosad (LP2M IAIN Sultan Amai Gorontalo, 2025)
This paper discusses a comparative study of educational systems between developing and developed countries, focusing on differences in system design, quality, and management strategies. Education serves as a key indicator of national progress because it plays a crucial role in developing qualified human resources. Developing countries often face challenges such as limited educational facilities, low teacher quality, and unequal access to education. In contrast, developed countries possess well-planned, technology-based education systems that balance theory and practice. Singapore is presented as an example of a developed country that has successfully built an effective education system through curriculum alignment with labor market needs, an emphasis on STEM (Science, Technology, Engineering, and Mathematics), and teacher development through institutions like the National Institute of Education (NIE). The study reveals that education quality depends on management effectiveness, teacher professionalism, and strong government policy support. Thus, education plays a vital role as a determinant of a nation's advancement and societal welfare.